(3GdEJUGd GdaYGd aj EOGQI GdCYeGd (B/s - (3MehO, NVjQ cGXes ((3YeGf(B: s (3OGQ UaGA(B, s, 2009)
(3eaghe h WHjYI GdGJUGd , , THcGJ GdGJUGd ,GdGJUGd Hjf GdKbGaGJ GdeNJdaI , aGYdjI GdGJUGd Hjf GdGaQGO , egGQGJ GdGSJeGY , egGQGJ GdcJGHI h GdbQGAI , GdebGHdGJ GdTNUjI , GOGQI GdGLJeGYGJ , GOGQI GdeDJeQGJ , GYOGO h JMdjd GdJbGQjQ GdGOGQjI h GdeGdjI , JWhQ hSGFd GdGJUGds
(3eQGLY U(B.269s
Keywords: (3EOGQI GdCYeGds; (3GdGJUGd GdLeGgjQjs; (3GdGJUGdGJ GdGOGQjIs